2019
DOI: 10.1136/bmjgh-2018-001144
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime economic impact of the burden of childhood stunting attributable to maternal psychosocial risk factors in 137 low/middle-income countries

Abstract: IntroductionThe first 1000 days of life is a period of great potential and vulnerability. In particular, physical growth of children can be affected by the lack of access to basic needs as well as psychosocial factors, such as maternal depression. The objectives of the present study are to: (1) quantify the burden of childhood stunting in low/middle-income countries attributable to psychosocial risk factors; and (2) estimate the related lifetime economic costs.MethodsA comparative risk assessment analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 37 publications
1
29
0
3
Order By: Relevance
“…4 The sample size with anthropometric measures was slightly smaller (n = 1,412 overall; n = 1,206 low CMD; n = 206 high CMD). 5 Coded as positive if mother reported that child suffered from cough, fever or diarrhea in the previous 2 weeks. 6 Ratio of individuals aged <15yrs or >55yrs to those aged 16-55yrs.…”
Section: Multidimensional Predictors Of Common Mental Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The sample size with anthropometric measures was slightly smaller (n = 1,412 overall; n = 1,206 low CMD; n = 206 high CMD). 5 Coded as positive if mother reported that child suffered from cough, fever or diarrhea in the previous 2 weeks. 6 Ratio of individuals aged <15yrs or >55yrs to those aged 16-55yrs.…”
Section: Multidimensional Predictors Of Common Mental Disordersmentioning
confidence: 99%
“…Common mental disorders (CMD) such as depression and anxiety are important yet often neglected issues in high poverty contexts, where problems that are easier to see, measure, or treat often draw public health investments. Depression is the leading cause of disability worldwide [1] and CMD have been linked to lost productivity [2], increased healthcare expenses [3], poor physical and cognitive development in children [4], and high long-term costs [5]. In India, a systematic review found that 20% of mothers suffer from postpartum depression [6], but little information is available on the prevalence of CMD in mothers beyond the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate infant and young child feeding practices increase the risk of morbidity and mortality, especially in low resource settings. Moreover, childhood morbidity has been associated with maternal depression symptoms in such settings [4]. The prevalence of postnatal maternal depression symptoms in 2015 was 50% in South Africa [5] while in Zimbabwe the prevalence increased from 16 to 34% between 1995 and 2015 [6].…”
Section: Introductionmentioning
confidence: 99%
“…While the national and local government has been implementing many welfare schemes in the key domain of livelihood, health, nutrition, education for reduction of poverty, the effect of these schemes varied by type of services, outcome variable and country-specific [6][7][8][9]. Malnutrition among children is positively associated with poverty and has many adverse short and long term consequences; illhealth, cognitive impairment, childhood mortality in short term and the likelihood of developing the noncommunicable diseases in the long term [10][11][12][13][14][15]. Nutrition sensitive interventions for children are increasingly emphasized in the poverty reduction programme of developing countries.…”
Section: Introductionmentioning
confidence: 99%